Procyclical Stocks Earn Higher Returns - Goetzmann, William N.,Watanabe, Akiko,Watanabe, Masahiro (National Bureau of Economic Research, 2024)
We find that procyclical stocks, whose returns comove with business cycles, earn higher average returns than countercyclical stocks. We use almost a three-quarter century of real GDP growth expectations from economists' surveys to determine forecasted economic states. This approach largely avoids the confounding effects of econometric forecasting model error. The loading on the expected real GDP growth rate is a priced risk measure. A fully tradable, ex-ante portfolio formed on this loading generates a procyclicality premium that is statistically significant, economically large, long-lasting over a few years, and independent of the size, book-to-market, and momentum effects
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Finanzmarkt; Konjunktur; Börsenkurs; Rendite; Wirtschaftsprognose; Business Fluctuations; Cycles; Financial Markets and the Macroeconomy; Asset Pricing; Trading Volume; Bond Interest Rates; Information and Market Efficiency; Event Studies; Insider Trading; Financial Forecasting and Simulation